Identifying stable loci for stigma exsertion rate by co-located QTL analysis in rice - Jiajun Chen; Linjiao Li; Hongli Ma; Linghong Li; Yi Liu; Yaxuan Xia; Jinjian Fan; Shilai Zhang; Quanya Tan (Euphytica, 2026)

Identification and expression analysis of BAG gene family under salt and cold stress in soybean - Ping Sun; Zihan Kong; Xin Liu; Tiansheng Liu; Lina Jiang; Shimeng Xu; Hongli He; Zhiyao Dong; Xingzheng Zhang (Euphytica, 2026)

QTL mapping and candidate gene analysis of berry and cluster traits in table grapevine bred for warm climates - Guilherme F. Simiqueli; Fernanda Golin Panisson; João Dimas Garcia Maia; Leo Duc Haa Carson Schwartzhaupt da Con; Vera Quecini; Dario Grattapaglia; Patricia Ritschel (Euphytica, 2026)
Table grapes are a valuable fruit crop worldwide. Warm climates are emerging as important global production suppliers. Traditional grapevine cultivars are poorly adapted to higher temperatures and other abiotic factors of warm zones, conditions increasingly common in temperate areas due to climate change. Understanding the genetic architecture of production traits in breeding families developed for warm climates is crucial to advance cultivar development. The current work mapped and investigated genomic regions controlling cluster and berry traits in two table grape biparental populations developed for warm climates. Progenies were phenotyped over at least three seasons for three cluster and nine berry traits. Individuals were genotyped with 1904 single nucleotide polymorphism (SNP) markers using the EMBRAPA Multi65K multi-species Illumina Infinium chip. Linkage maps for the families were built, aligned to the most recent chromosome-scale Vitis genome and used for multivariate Bayesian QTL mapping to identify 10 QTLs in family 1630 and nine in family 1637. QTL reliability was assessed by its reproducibility in analyses using different repetitions and models. QTLs were found on chromosomes 8, 11, 15 and 17 in line with reliable QTLs mapped in previous studies, providing additional evidence for stable effect loci for berry and cluster architecture traits. Functional gene enrichment analyses of the mapped QTLs identified viable candidate genes for the investigated traits, including specialized metabolism genes for astringency and cytoskeleton components for berry length. Flanking SNPs to the mapped QTLs could allow accelerated breeding by increasing selection intensity within-family on yet to be phenotyped seedlings.

Identification of both shared and isolate-specific QTL and underlying candidate genes for Vanilla planifolia resistance to Fusarium root and stem rot - Quentin Da Silva; Lucy Marcadé; Elisa Hoareau; Déborah Turpin; Betty Casimir; Katia Jade; Félicien Favre; Pascale Besse; Carine Charron (Euphytica, 2026)
Vanilla planifolia suffers major losses from root and stem rot (RSR) caused by Fusarium oxysporum f. sp. radicis-vanillae (Forv), amplified by low genetic diversity. We dissected quantitative resistance by phenotyping a selfed population AF_CR0040 (n = 115) inoculated with three Forv isolates (Fo166, Fo254, Fo297). Five traits were scored: symptoms at 5, 10 and 15 days post-inoculation (dpi), the area under the disease progress curve (AUDPC) and the day of mycelium appearance (d.myc). Multiple quantitative trait locus (QTL) mapping (MQM) was realized on a high-density genotyping-by-sequencing (GBS) map. QTL were anchored to the CR0040 genome to identify candidates. We detected 121 QTL across isolates and traits, explaining 2.5 to 21.8% of phenotypic variance, including 39 major loci (≥ 10%). Stable hotspots were shared by several isolates and traits, isolate-specific loci were also identified. Standardizing effects showed 44% of QTL carried favorable alleles (51% among major loci), with frequent dominance, consistent with transgressive segregation. In total, 837 genes lay within QTL windows. Top multi-QTL candidates encoded a calcium-dependent ADP-ribosylation factor GTPase-activating protein (ARF-GAP), three ATP-binding cassette (ABC) transporters, a basic helix-loop-helix (bHLH) transcription factor, a uridine kinase, and a leucine-rich repeat receptor-like kinase (LRR-RLK). These findings reveal coexisting generalist and isolate-specific resistance modules and provide genome-anchored targets for functional validation, gene pyramiding, and marker-assisted selection in vanilla.